Mechanisms of retinoic acid-mediated inhibition of estrogen-induced transcription and growth in human breast carcinoma cells. - Deonarine, Dave. (University of Ottawa (Canada), 1996)
Retinoids have been shown to inhibit the growth of estrogen receptor-positive human breast cancer cells. In this study, it is shown that all-trans-retinoic acid (RA) inhibits the growth of MCF-7 cells by 60%. In these cells, we also found that RA inhibited estrogen-induced transcription. In transient transfection experiments using the vitellogenin-estrogen response element-CAT reporter construct, RA inhibited estrogen-induced transcription by 55%. Cotransfection of wildtype RAR$\alpha$ resulted in a 75% inhibition of estrogen-induced transcription. In order to investigate the mechanisms involved in RA-mediated inhibition of transcription, deletion mutants of RAR$\alpha$ were constructed. Point mutants of RAR$\alpha$ were also evaluated to determine their effects on RA-mediated inhibition of estrogen-induced transcription. Cotransfection of RAR$\alpha$ deletion mutants terminating after amino acid 414 resulted in wildtype inhibition. Using mutants terminating before amino acid 412, the inhibition was significantly reduced. RAR$\alpha$ mutants lacking amino acids 413 and 414 also showed significantly decreased inhibition. The amino acids 413 and 414 correspond to the activating function-2 (AF-2) region in the C-terminus of the RAR$\alpha.$ These results suggest that the RA-mediated inhibition of estrogen-induced transcription in human breast carcinoma cells is mediated by the AF-2 region of the RAR$\alpha.$ MCF-7 cells, stably transfected with a dominant negative RAR$\alpha,$ are growth inhibited by only 25% compared to 60% for untransfected or mock-transfected cells. Taken together, these results suggest that RA-mediated inhibition of estrogen-induced transcription is mediated by the AF-2 region of the RAR$\alpha$ and may play a role in RA-induced inhibition of estrogen receptor-positive human breast cancer cell growth.
Keywords: Health Sciences, Pharmacology.